Electrode Wear Rate On Electrical Discharge Machining of Titanium Alloys (Ti-6Al-4V) At Different Peak Current and Pulse Duration by Using Modified RBD Palm Oil as Dielectric Fluids - Supawi, Aiman; Ahmad, Said; Talib, Norfazillah; Lee Woon Kiow,; Ho Fu Haw,; Mohd Joharudin, Nurul Farahin (International Journal of Integrated Engineering, 2022)
Electrical Discharge Machining (EDM) is a machining process in terms of thermoelectric that removes metal by discharging a discrete sparks series of the metal and workpiece. The cutting tool in EDM has used an electric spark to cut the workpiece of sample and produce the finished part to the demanded shape. Vegetable oil as the dielectric fluid is one way to ensure EDM's long-term viability because it is environmentally friendly and biodegradable. The main objective of this preliminary study is to compare the uses of modified bio-degradable and conventional dielectric fluid performance for a titanium alloy (Ti-6Al-4V) with a copper (Cu) electrode using a sustainable EDM process in terms of electrode wear rate (EWR). To achieve a concentration of viscosity rate as kerosene fluids, RBD palm oil has been transesterified. The effect of EWR of kerosene and modified RBD palm oil as dielectric fluids was investigated in this paper for response variables of pulse duration (ton) of 50, 100, and 150µs, and peak current (Ip) of 6, 9, and 12A. The morphology of the copper electrode, as well as the migration of workpiece material elements to the tool electrode, were studied by using scanning electron microscopy (SEM). The lowest EWR was recorded at Ip=6A with ton=150µs, which is 0.0416mm3/min and 0.0432mm3/min, and the highest EWR was recorded at Ip=12A with ton=50µs, which is 0.1725mm3/min and 0.2324mm3/min, for modified RBD palm oil compared to kerosene, respectively. The EWR rises as the peak current rises, but it decreases as the pulse duration increases. The uses of modified RBD palm oil shows slightly different results compared to kerosene.